2014
DOI: 10.4103/0300-1652.140383
|View full text |Cite
|
Sign up to set email alerts
|

Communicating tobacco health risks: How effective are the warning labels on tobacco products?

Abstract: Background:Health hazards of tobacco are well known but only small numbers of tobacco users are fully aware of the harmful effects of tobacco. Warning labels on tobacco products are an effective way of communicating the consequences of tobacco use and bring about behavioural changes like quitting and reducing the tobacco consumption. So the present study was conducted to investigate the awareness and effectiveness of warning labels on tobacco products among health and non-healthcare professional of Barwala, Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Most waterpipe smokers believed that waterpipe smoking is less harmful, less addictive, and contains less nicotine than cigarettes, providing further evidence of the need to adopt specific regulations that increase awareness about the harms of waterpipe smoking and motive smokers to quit. There is extensive evidence that health-warning labels on cigarette packs raise awareness of health consequences from smoking (Chopra et al 2014; Hammond et al 2006), which supports the need for health warnings for waterpipe tobacco. However, due to the unique of the waterpipe device, regulation of waterpipe-specific health warnings has to take into consideration this uniqueness.…”
Section: Discussionmentioning
confidence: 98%
“…Most waterpipe smokers believed that waterpipe smoking is less harmful, less addictive, and contains less nicotine than cigarettes, providing further evidence of the need to adopt specific regulations that increase awareness about the harms of waterpipe smoking and motive smokers to quit. There is extensive evidence that health-warning labels on cigarette packs raise awareness of health consequences from smoking (Chopra et al 2014; Hammond et al 2006), which supports the need for health warnings for waterpipe tobacco. However, due to the unique of the waterpipe device, regulation of waterpipe-specific health warnings has to take into consideration this uniqueness.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown people preferring text messages in the local language. [ 18 ] This is an important reason for preference of PHWs especially by those not knowing English or Hindi.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] It has been felt earlier by the people that stronger and scarier PHWs are needed to make these more effective. [ 18 21 ]…”
Section: Discussionmentioning
confidence: 99%
“… 57 In many LMICs and MUIC, research and policy energy has been directed towards other simple and effective tobacco control interventions, such as increasing taxes 58 or pictorial health warnings such as in Asia 59 and Nigeria. 60 However, for LMIC, it may take many years, and much supporting research of various kinds, such as in Australia, to introduce plain packaging. Given the dearth of papers from LMICs, and the time it takes to generate high-level research, research needs to be started now.…”
Section: Discussionmentioning
confidence: 99%